Albania on the Move Links between Internal and International Migration - Vullnetari, Julie (IMISCOE Research, 2012)
Starting from a cluster of villages in southeast Albania, Albanian-born British scholar Julie Vullnetari follows rural migrants to domestic urban destinations such as Tirana and abroad to Thessaloniki in Greece. Vullnetari has conducted more than 150 interviews, and drawing upon this rich empirical material, she offers a profound account of Albanian migration from start to finish. A rare, exhaustive overview of Albania's post-communist internal and international migrations, Albania on the Move is a powerful combination of ethnography and multifaceted academic analysis, grounded in the personal experience of the author.